2022
DOI: 10.1021/jacs.2c01103
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Medium-Sized-Ring Lactones via Iridium-Catalyzed Z-Retentive Asymmetric Allylic Substitution Reaction

Abstract: Medium-sized rings are important structural units, but their synthesis, especially in a highly enantioselective manner, has been a great challenge. Herein we report an enantioselective synthesis of medium-sized-ring lactones by an iridium-catalyzed Z-retentive asymmetric allylic substitution reaction. The reaction features mild conditions and a broad substrate scope. Various eight- to 11-membered-ring lactones can be afforded in moderate to excellent yields (up to 88%) and excellent enantioselectivity (up to 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…5 Owing to their structural diversity and unique biological activities, synthetic protocols of medium-sized lactones always attract the attention of medicinal chemists. 6 In contrast to the synthesis of 5-to 6-membered ring lactones, the efficient construction of mediumsized lactones remains a formidable challenge due to their inherent entropic factors and unfavorable transannular interactions. 6c Over the past decade, numerous synthetic strategies have been applied to prepare medium-sized lactones, including intramolecular esterification of hydroxycarboxylic acids, 1b intramolecular carbonyl hydroacylation of benzaldehydes, 7 metal-catalyzed cycloisomerization of alkynoic acids, 8 organocatalyzed halolactonization of olefinic acids, 9 bond-cleaving/ ring-expansion of oxindoles with zwitterion precursors 10 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…5 Owing to their structural diversity and unique biological activities, synthetic protocols of medium-sized lactones always attract the attention of medicinal chemists. 6 In contrast to the synthesis of 5-to 6-membered ring lactones, the efficient construction of mediumsized lactones remains a formidable challenge due to their inherent entropic factors and unfavorable transannular interactions. 6c Over the past decade, numerous synthetic strategies have been applied to prepare medium-sized lactones, including intramolecular esterification of hydroxycarboxylic acids, 1b intramolecular carbonyl hydroacylation of benzaldehydes, 7 metal-catalyzed cycloisomerization of alkynoic acids, 8 organocatalyzed halolactonization of olefinic acids, 9 bond-cleaving/ ring-expansion of oxindoles with zwitterion precursors 10 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric Ir­(I)-catalyzed allylic alkylation reactions have attracted significant attention in recent years due to their high regio- and enantioselectivity and are a most versatile and powerful method to construct C–C and C-heteroatom bonds. Generally, amine or enolate formed by deprotonation of carbonyl precursors has been used as nucleophiles to produce chiral, branched products (Scheme a). Application of prochiral nucleophiles in these reactions would produce vicinal chiral stereocenters, but the stereochemical control of reactions with a single Ir­(I) catalyst is difficult. The introduction of a second catalyst with the aim of catalyzing the generation of a chiral nucleophile which could participate this Ir­(I)-catalyzed substitution is an effective but challenging solution. Carreira and co-workers developed the first dual enamine catalysis and Ir­(I)-catalyzed allylic substitution to provide a stereodivergent access to four stereoisomers (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The synthesis of these heterocycles in enantiopure form is therefore a key target, and can be particularly challenging for medium rings. [3,4] Existing approaches to this class of compound include the iridium catalyzed enantioselective synthesis of indole-annulated medium rings via an allylic dearomatization/retro-Mannich/ hydrolysis cascade, [5,6] palladium catalyzed [5+2] cycloaddition of vinyl ethylene carbonates with α-diazoketones, [7] and enantioselective ring expansion of strained rings. [8] Shibata et al demonstrated an asymmetric synthesis of CF 3 -substituted nine-membered heterocycles by Pd-catalyzed decarboxylative ring expansion strategy, [9] and the enantioselec-tive construction of medium ring bridged biaryls is noteworthy.…”
mentioning
confidence: 99%